If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -8 + 2 = 4x + 20 Reorder the terms: -8 + 2 + -6x = 4x + 20 Combine like terms: -8 + 2 = -6 -6 + -6x = 4x + 20 Reorder the terms: -6 + -6x = 20 + 4x Solving -6 + -6x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + -6x + -4x = 20 + 4x + -4x Combine like terms: -6x + -4x = -10x -6 + -10x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 -6 + -10x = 20 + 0 -6 + -10x = 20 Add '6' to each side of the equation. -6 + 6 + -10x = 20 + 6 Combine like terms: -6 + 6 = 0 0 + -10x = 20 + 6 -10x = 20 + 6 Combine like terms: 20 + 6 = 26 -10x = 26 Divide each side by '-10'. x = -2.6 Simplifying x = -2.6
| 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x | | 3(50+25)= | | 19y=76 | | 4.87=m+0.87 | | 3(x-6)=9(x-2) | | 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 | | 63=-15+x | | 6.4x=.064 | | 6-x=4-.5x | | 2x^3+16y^3=0 | | 2x-11=83 | | 63=-15+4 | | x/2-9=-5 |